Inclusive Leadership Negotiating Gendered Spaces (Palgrave Studies in Leadership and Followership,, 2018)
Examining perceptions of leaders which are dependent on social and cultural contexts, this edited collection argues that in order to thrive and to understand the future business landscape, leaders must be inclusive and create followership. With existing research tending to conflate leadership roles with notions of masculinity and agency, this study provides examples of how to alter and challenge prevalent stereotypes and ultimately contribute to greater organisational effectiveness. Addressing the under-representation of women in leadership roles, contributions explore inclusivity and exclusivity in leading organisations, the politics of gendered differences and the value of leader-follower dynamics. Inclusive Leadership will be of great use to business leaders, employees, policy-makers, and academics seeking practical implications for formulating effective leader-follower strategies in organisations.